On the Effectiveness of the Solution-Focused Approach and Coaching in the Work of Social Services - Małgorzata Szpunar (Institute of Social Affairs of the Pedagogical University of Cracow, 2021)
The article is a comparative analysis of two methods of working with a social assistance client: coaching and solution-focused approach. It describes the stages of the methodological procedure, and shows the approach to the motivation to change in both approaches. Showing the differences between internal and external motivation in the case of social assistance clients is particularly important, as they are often people characterized by learning helplessness and with low social competence. Therefore, working on change is extremely difficult, and social and legal expectations generate many paradoxes of professional action. The solution, however, is not to control and monitor the customers' progress, but to change the approach of defining goals for change for customers. In coaching and PSR, key goals are the client's goals and this article explains the rationale behind this position. Then, it describes the assumptions of both approaches and presents similar techniques used in working with the client. These techniques are easy to adapt to the methodical work of social workers and assistants when they share the assumption that the client is the expert of their life, and thus of change and the path to change. It describes the structure of the change process in both approaches. The article is intended to encourage such an approach to working with clients, as it is effective, as well as releasing social workers from responsibility for clients' failures, protecting against burnout, and easy to apply. In addition, many institutions of social assistance are leaning towards working with these methods, towards formulating goals in line with harm reduction, rather than radical changes.  Keywords: coaching, solution-focused approach, methodological procedure, motivation to change, professional development O skuteczności podejścia skoncentrowanego na rozwiązaniach i coachingu w pracy służb społecznych Artykuł zawiera analizę porównawczą dwóch metod pracy z klientem pomocy społecznej: coachingu oraz podejścia skoncentrowanego na rozwiązaniach. Opisano w nim etapy postępowania metodycznego oraz stosunek do motywacji do zmiany w obu podejściach. Pokazanie różnic między motywacją wewnętrzną i zewnętrzną w przypadku klientów pomocy społecznej jest szczególnie ważne, bo często są to osoby o wyuczonej bezradności oraz niskich kompetencjach społecznych. Praca nad zmianą jest więc wyjątkowo trudna, a oczekiwania społeczne i prawne generują wiele paradoksów działania profesjonalnego. Rozwiązaniem jednak nie jest kontrola i monitorowanie postępów klienta, ale zmiana podejścia wobec definiowania celów zmiany u klientów. W coachingu oraz PSR kluczowe cele to cele klienta i w artykule przedstawiono najpierw uzasadnienie takiego stanowiska. Następnie opisano założenia obu podejść i zaprezentowano podobne techniki wykorzystywane w pracy z klientem. Techniki te są proste do adaptacji w pracy metodycznej pracowników socjalnych i asystentów, gdy zakładają oni, że to klient jest ekspertem swojego życia, a tym samym zmiany i drogi do zmiany. W artykule scharakteryzowano strukturę procesu zmiany w obu podejściach. Celem podjętych rozważań jest zachęcenie do zaprezentowanego podejścia w pracy z klientami. Jest ono nie tylko skuteczne, lecz także zwalnia z odpowiedzialności pracowników socjalnych za porażki klientów, chroni przed wypaleniem zawodowym, a ponadto jest proste w zastosowaniu. Poza tym wiele instytucji pomocy społecznej skłania się ku pracy przedstawionymi metodami, tj. ku formułowaniu celów zgodnie z redukcją szkód, a nie radykalnymi zmianami.